Synchronization of the Transfer of the Indonesian State Capital According to Law Number 3 of 2022 Concerning the State Capital with the 1945 Constitution and Applicable Positive Laws - Ferdinand Nicholas (Pelopor Publikasi Akademika, 2023)
Until now, the capital city of Indonesia is the Special Capital Region of Jakarta (DKI Jakarta). Jakarta as the capital is the center of everything that makes Jakarta a big burden as the capital of Indonesia. President Joko Widodo moved the capital from Jakarta to Kalimantan under the name